A Network Meta-Analysis of Long-Acting Muscarinic Antagonist (LAMA) and Long-Acting β(2)-Agonist (LABA) Combinations in COPD - Sion, Katya Y. J. (Pulm Ther, 2017)
INTRODUCTION: Comparative data on the efficacies of long-acting muscarinic antagonist (LAMA) and long-acting β(2)-agonist (LABA) combinations for the treatment of moderate-to-very-severe chronic obstructive pulmonary disease (COPD) are limited. The aim of this Bayesian network meta-analysis (NMA) is to assess the relative efficacies of available open combinations (delivered via separate inhalers) and fixed-dose combinations (FDCs, delivered via a single inhaler). METHODS: We conducted a systematic literature review with the aim of identifying randomized controlled trials (RCTs) of ≥8-week duration in adults aged ≥40 years with COPD that compared LAMA + LABA combinations with each other, with tiotropium (TIO), or with placebo. Data on changes from baseline in trough forced expiratory volume in 1 s (FEV(1)) and on St George’s Respiratory Questionnaire (SGRQ) total score, the Transition Dyspnea Index (TDI) focal score, and rescue medication use at 12 and 24 weeks were extracted from these RCTs and analyzed using a NMA in a Bayesian framework. RESULTS: Data from 44 RCTs were included in the NMA. All FDCs showed improvements relative to placebo in terms of trough FEV(1), SGRQ total score, and TDI focal score above clinically relevant thresholds, with the exception of TIO/olodaterol and aclidinium/formoterol, both of which failed to show clinically relevant improvements in SGRQ score at 24 weeks. All FDCs demonstrated reduced rescue medication use versus placebo. Open combinations demonstrated improved efficacy in all outcomes versus placebo, but these improvements did not consistently exceed clinically relevant thresholds for SGRQ and TDI scores. All once-daily FDCs showed improved efficacy versus TIO, but improvements were less consistently observed versus TIO with open dual combinations and combinations containing formoterol or salmeterol administered twice daily. Relative probabilities of improvement between FDCs highlighted potential between-class differences for trough FEV(1) but suggested little potential for differences in patient-reported outcomes. CONCLUSION: LAMA + LABA combinations generally showed improved outcomes versus placebo and TIO. FDCs appeared to perform better than open dual combinations. A potential effectiveness gradient was observed between FDCs for objectively assessed functional outcomes, although further prospective trials are required to confirm these findings. FUNDING: GSK. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s41030-017-0048-0) contains supplementary material, which is available to authorized users.